Diagnostic accuracy of patient interview items and clinical tests for cervical radiculopathy. (June 2021) - Sleijser-Koehorst, Marije L.S.; Coppieters, Michel W.; Epping, Rob; Rooker, Servan; Verhagen, Arianne P.; Scholten-Peeters, Gwendolyne G.M.
Abstract: Objective: To determine the diagnostic accuracy of patient interview items and clinical tests to diagnose cervical radiculopathy. Design: A prospective diagnostic accuracy study. Participants: Consecutive patients ( N  = 134) with a suspicion of cervical radiculopathy were included. A medical specialist made the diagnosis of cervical radiculopathy based on the patient's clinical presentation and corresponding Magnetic Resonance Imaging findings. Participants completed a list of patient interview items and the clinical tests were performed by a physiotherapist. Main outcome measures: Diagnostic accuracy was determined in terms of sensitivity, specificity, and positive (+LR) and negative likelihood ratios (−LR). Sensitivity and specificity values ≥0.80 were considered high. We considered +LR ≥ 5 and −LR ≤ 0.20 moderate, and +LR ≥ 10 and −LR ≤ 0.10 high. Results: The history items 'arm pain worse than neck pain', 'provocation of symptoms when ironing', 'reduction of symptoms by walking with your hand in your pocket', the Spurling test and the presence of reduced reflexes showed high specificity and are therefore useful to increase the probability of cervical radiculopathy when positive. The presence of 'paraesthesia' and 'paraesthesia and/or numbness' showed high sensitivity, indicating that the absence of these patient interview items decreases the probability of cervical radiculopathy. Although most of these items had potentially relevant likelihood ratios, none showed moderate or high likelihood ratios. Conclusions: Several patient interview items, the Spurling test and reduced reflexes are useful to assist in the diagnosis of cervical radiculopathy. Because there is no gold standard for cervical radiculopathy, caution is required to not over-interpret diagnostic accuracy values.